Relacao entre antropometria, desempenho físico e estatística de jogo em jogadores jovens de elite de basquetebol - Gomes, J. H.; Gambaro Chaves, R.; Evangelista, A.; Charro, M. A.; Sales Bocalini, D.; Figueira Junior, A. J. (Revista Brasileira de Ciência e Movimento, 2015)
To diagnose anthropometric and physical performance characteristics of the Brazilian national basketball U19, and link these variables to the set of technical performance during the world championship. Twelve elite basketball players, aged 18.6 ± 0.7 years, body mass 91.3 ± 8.7 kg, height of 195.2 ± 10.2 cm and fat percentage of 11.4 ± 1.51% in the study. Physical performance tests were run 20m (C20), running T40m (T40) and Yo-Yo Intermittent Recovery I (Yo-yo RI). Through the game statistics, the technical performance indicators set were analyzed. The statistical analysis was descriptive statistics as the mean value, standard deviation, maximum and minimum values. We used the Pearson correlation coefficients between anthropometric values, physical performance and the technical performance of games. The correlation level of significance was p <0.05. The results were expressed as mean, standard deviation, maximum and minimum, being C20 = 2.97 ± 0,14s, 3,23s and 2,79s, T40 = 8.67 ± 0,41s, 9,72s and 8,29s and Yo-yo RI = 1173 ± 291,1m, 1760m and 800m. Positive and significant correlations with body mass of the C20 were identified (r = 0.72), height (r = 0.79), percentage of fat (r = 0.79) and fat mass (r = 0.81); and T40 with height (r = 0.72) and percentage fat (r = 0.72). We found no significant correlations between the physical performance tests and technical performance indicators game. The findings of this study suggest that the success and unsuccess technical performance in a short championship are apparently associated with the technical and tactical ability and decision making of the players than the level of physical performance